Improving teaching self-efficacy for teachers in inclusive classrooms in Hong Kong. Issue 11 (1st November 2016) - Chao, Chih Nuo Grace; Forlin, Chris; Ho, Fuk Chuen
ABSTRACT: This study investigated changes in teacher self-efficacy for inclusive practice using a mixed method research design. Participants were 417 in-service teachers in Hong Kong taking a 1-week basic teacher-training course about inclusive education. Data were collected pre and post participation in the course using the Teacher Efficacy for Inclusive Practices Scale (TEIP). A series of five in-depth focus-group interviews provided greater clarification of the perceptions and efficacy issues of teachers. The best predictors to participants' teaching self-efficacy were confidence in teaching students with special education needs (SEN) and knowledge of legislation and policies for inclusive practice. From the focus-groups, results demonstrated a more positive attitude change towards students with SEN with a number of essential factors emerging as highly beneficial for inclusive teaching in Hong Kong (i.e. caring and love, school environment and curriculum adaption). The discussion considers the role of short training programmes as an appropriate means to improving self-efficacy for teaching within inclusive classrooms in Hong Kong.